Sacred Mound, Holy Rings Silbury Hill and the West Kennet Palisade - Whittle, Alasdair (Oxbow Books, 1997)
The excavations at Silbury Hill in the late 1960s were broadcast to the world on television and generated a huge amount of excitement, but until now have not been published. This report gives a full account of the excavation and discusses the archaeological and environmental evidence from the tunnel, the ditch section and the cuttings on the top of the mound, as well as the radiocarbon dates. Neolithic enclosures at nearby West Kennet have been the subject of research excavations since 1987, carried out by Cardiff university. One is a nearly circular double enclosure that straddles the present Kennet, the other is a larger elliptical enclosure. The character of the palisades, their construction, the finds and the radiocarbon dates are fully reported. Very importantly there is an extensive discussion of the interpretation of Silbury Hill and the enclosures and of their relation to each other and to the other features of the Neolithic landscape: the Sanctuary, the West Kennet Avenue and Avebury itself.